Effect of thermal elastohydrodynamic lubrication on vibration characteristics of ball bearing with local defect. (September 2022) - Wang, Yubo; Yan, Changfeng; Lu, Zunyou; Liu, Yaofeng; Wu, Lixiao
The vibration response of ball bearing with local defect is closely associated with its lubrication condition. The previous bearing dynamic models were mainly established based on the idealised lubrication conditions, which may not uncover the influence of thermal effect of lubricant on vibration characteristics of defective bearing. This paper presented the influence of thermal effect on elastohydrodynamic lubrication (EHL) performances of ball bearing and the vibration characteristics of defective bearing under thermal EHL. Considering the point contact thermal EHL and the time-varying displacement excitation, a dynamic model of ball bearing with a localised defect on outer raceway was developed. The model was validated by the experimental results. Compared with isothermal EHL, the simulation results with thermal EHL reveal larger pressure and thinner film thickness in the ball-raceway contact interface. Meanwhile, the rotating speed and radial load have significant effects on the thermal EHL performance of ball bearing. The effects of three contact conditions (dry friction, isothermal and thermal EHL) on vibration amplitude of defective bearing in frequency domain are discussed. The results show that the lubricant could improve the vibration of defective bearing, whereas the addition of thermal effect of EHL could increase the vibration amplitude and deteriorate the lubricating performance. The model is beneficial to the bearing model optimisation and the rational selection of lubricants.